2002
DOI: 10.1037/0022-006x.70.3.569
|View full text |Cite
|
Sign up to set email alerts
|

Biobehavioral approaches to the treatment of essential hypertension.

Abstract: Despite recent advances in the medical management of hypertension, chronically elevated blood pressure remains a major health problem in the United States, affecting almost 50 million Americans. It is widely recognized that lifestyle factors contribute to the development and maintenance of elevated blood pressure. This article critically reviews current approaches to the nonpharmacological treatment of high blood pressure and highlights outcome studies of exercise, weight loss and dietary modification, and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 211 publications
(248 reference statements)
0
19
0
3
Order By: Relevance
“…The mean value of the three blood pressure measurements of the first clinical visit were used as a baseline. However, earlier studies of treating hypertension with relaxation therapies found it critical for future studies to have an extended baseline measurement period of over 3-4 weeks in order to reduce the potentially confounding effects that may occur when participants adapt to the measurement procedure (Blumenthal et al 2002). A probable explanation to the significant main effect of time might be the lack of an extended baseline measurement period as described above, and that the participants of both groups were simply more relaxed during the second (post-treatment) visit to the clinic due to adaptation to the situation in which the measurements were done.…”
Section: Discussionmentioning
confidence: 98%
“…The mean value of the three blood pressure measurements of the first clinical visit were used as a baseline. However, earlier studies of treating hypertension with relaxation therapies found it critical for future studies to have an extended baseline measurement period of over 3-4 weeks in order to reduce the potentially confounding effects that may occur when participants adapt to the measurement procedure (Blumenthal et al 2002). A probable explanation to the significant main effect of time might be the lack of an extended baseline measurement period as described above, and that the participants of both groups were simply more relaxed during the second (post-treatment) visit to the clinic due to adaptation to the situation in which the measurements were done.…”
Section: Discussionmentioning
confidence: 98%
“…Considerando entonces, la recomendación Blumenthal et al (2002), es importante rehacer el estudio sin que los individuos sujetos hagan uso de medicamento, para que así se pueda confirmar los efectos positivos prevenientes exclusivamente del tratamiento preescrito por los autores.…”
Section: Discussionunclassified
“…Recent studies in psychoneuroimmunology and related psychological behaviors have determined that play activities, dance included, are beneficial to emotional health (Blumenthal, Sherwood, & Gullette, 2002;Dishman & O'Connor, 2009;Dubbert, 2002;KiecoltGlaser et al, 2002;Salmon, 2001;Smith & Ruiz, 2002). Specifically, stressful traumatic exposures amidst poor social support take a heavy toll not only on the functioning of the physical body, but also on an individual's psychological wellbeing.…”
Section: Immune Responses the Healing Experience In The Mourning Danmentioning
confidence: 95%